간호대학생의 감사성향, 간호전문직관이 생명의료윤리의식에 미치는 영향 - 홍소형; 오숙희 (다문화건강학회지, 2023)
Purpose: This study is a descriptive research study that sought toe identify the effects of the gratitude disposition and nursing professionalism of nursing students on their awareness of biomedical ethics. Methods: The subjects of the study were 200 nursing students from a university located in J city. The collected data were subjected to mean, standard deviation, correlation and regression analysis using SPSS 23.0. Results: The awareness of biomedical ethics showed a significant correlation with gratitude disposition and nursing professionalism(r=.26, p<.001, r=.31, p<.001). The factors influencing awareness of biomedical ethics included, grade 10.2%, gratitude disposition 15.9%, and nursing professionalism which had an explanatory power of 19.0%. Conclusion: To ensure awareness of biomedical ethics, it would be necessary to design and implement subject and extracurricular programs that include gratitude disposition and nursing professionalism, Also, grade-wise, systematic intervention would be essential to meet this objective. KCI Citation Count: 0